Explanatory models and animal health-seeking behavior for East Coast fever in rural Kenya: an ethnographic study - Muthiru, Ann W.; Muema, Josphat; Mutono, Nyamai; Thumbi, S. M.; Bukachi, Salome A. (Frontiers in Veterinary Science, 2024)
Explanatory models of disease focus on individuals' and groups' understandings of diseases, revealing a disconnect between livestock keepers and animal health providers. Animal health providers rely on models grounded in their veterinary training and experience. At the same time, livestock keepers may construct models based on traditional knowledge and their lived experience with East Coast fever in their cattle herds. To better understand East Coast fever and develop more efficient management strategies, this ethnographic study used the explanatory models framework to provide a structured way for comprehending and contrasting different beliefs and understandings of East Coast fever as perceived by the livestock keepers across the different livestock production systems. Multiple data collection methods were employed, including unstructured observations, 30 in-depth interviews (IDIs), 18 focus group discussions (FGDs), and 25 key informant interviews (KIIs). Adult cattle, calves and sheep were perceived as susceptible to East Coast fever. However, there were varying perceptions of livestock susceptible to East Coast fever in the different livestock production systems. East Coast fever was attributed to multiple factors including ticks, tsetse flies, mosquitos, birds, stagnant, dirty, or contaminated water, and livestock-wildlife interactions. However, some aspects were specific to the production system. Livestock keepers classified diseases based on observable signs, grouping diseases with similar signs under the same classification. Moreover, livestock keepers described different forms of East Coast fever ranging from treatable to fatal, which could be distinguished by the signs they presented. Self-treatment with drugs from the local agro-vet shops was the initial course of action during suspected cases of East Coast fever. Animal health practitioners were the last resort if self-treatment did not produce the desired outcome. Livestock keepers perceived avoidance of stagnant or contaminated water, tick control, and fencing as effective control measures for East Coast fever in their livestock herd. Very few livestock keepers were aware of an East Coast fever vaccine.Mechanistic explanation holds little significance in the control of East Coast fever. Instead, understanding and addressing livestock keepers' beliefs regarding ECF is crucial for promoting behaviors supporting interventions across the different livestock production systems.